Socio-Economic Analysis of Parents on the Practice of Providing Early Complementary Feeding to Infants Aged 6-12 Months in Tanjung Baru Village : A Cross-sectional Study - Haryanti, ⁠Ita; Yuriah, Siti (STIKes Al-Ma'arif Baturaja, 2025)
Early Complementary Feeding (ECF) is food or drink containing nutrients, which is given to infants or children aged 6-12 months to meet nutritional needs other than breast milk. Many factors are related to the provision of early ECF by mothers including knowledge, health and occupation of the mother, ECF advertisements, health workers, culture and socio-economics. The socio-economic status of the family influences mothers in providing complementary foods for breast milk too early. Parents think that, as long as the child feels they can eat. The purpose of the study was to analyze the relationship between socio-economic factors of parents and the practice of providing Early Complementary Feeding for breast milk in infants aged 6-12 months in Tanjung Baru Village in 2024. This study is a study that uses a quantitative method with a Cross Sectional approach. The sampling technique using purposive sampling obtained a sample size of 66 respondents. The location of this research is in Tanjung Baru Village. Data analysis using univariate analysis to determine the frequency distribution and bivariate analysis using the Chi Square test. The results of the Chi Square test obtained a ρ Value of 0.000 < (0.05). Significant factors for Early Complementary Food for Infants aged 6-12 months are knowledge (p=0.000), culture (p=0.000), education (p=0.000), income (p=0.000), and occupation (p=0.000). The conclusion of this study is that there is a relationship between the socio-economic status of parents and the practice of providing Early Complementary Feeding for Infants aged 6-12 months in Tanjung Baru Village in 2024. It is hoped that midwives can provide an appeal to the village to increase awareness for mothers about Early Complementary Feeding for Infants aged 6-12 months in Tanjung Baru Village and always provide care according to the established midwifery service standards in accordance with the authority of the midwife.